CHRONOLOGY OF MULTIPHASE EMPLACEMENT OF THE SALMI RAPAKIVI GRANITE-ANORTHOSITE COMPLEX, BALTIC SHIELD: IMPLICATIONS FOR MAGMATIC EVOLUTION - Amelin Y.V.; Larin A.M.; Tucker R.D. (My University, 1997)
The U-Pb dating of 18 samples, representing the principal rock types of the 4000 km2 Salmi anorthosite-rapakivi granite complex and its satellite Uljalegi pluton, southeastern Baltic (Fennoscandian) Shield, reveals that six temporally distinct episodes of igneous activity occurred in a timespan of 17 million years. From oldest to youngest they are: (1) gabbronorite and monzonite at 1546.7 Ma; (2) syenogranite at 1543.4 Ma; (3) early wiborgite and pyterlite at 1540.6–1537.9 Ma; (4) biotite granite and more evolved granite at 1538.4–1535 Ma; (5) late pyterlite at 1535.2 Ma; (6) olivine gabbro and biotite-amphibole granite at 1530 Ma. The resolvable intervals between magmatic episodes are 3.5–5.0 million years. Early wiborgite and pyterlite (3, above) and biotite granite (4, above) probably crystallized from multiple magma intrusions. Age differences of 3.4±1.5 million years between zircon and baddeleyite in olivine gabbro (6, above) are probably a result of xenocrystic origin of baddeleyite extracted from an earlier mafic phase of the Salmi complex. The ages and chemical features of early and late zircon populations, together with our modeling of magma crystallization and zircon growth, show that the duration of magma crystallization and Pb-diffusion in zircon was short lived and insignificant compared to the precision of dating of about ±1–2 million years. Hence, the range of U-Pb ages for each of the major rock types may approximate the emplacement intervals of their respective magmas. Average rate of magma emplacement was about 0.01 km3/year for the most voluminous phase of early biotite-amphibole rapakivi granite, and about 0.0024 km3/year for the Salmi complex as a whole. Compositional changes of the Salmi magmas over time are in agreement with the model of magmatism related to lithospheric extension.